Map of the United States, and Territories. Together with Canada &c. - Wm. M. Bradley & Bros. (Wm. M. Bradley & Bro., 1887)
Map shows railroads, major cities and towns, major roads to the West, areas of Native American habitation, "Indian Territory," "Dacotah Territory," and boundary between Mexico and U.S. set in 1848 and 1854. Inset: "Island of Newfoundland." Relief shown by hachures and spot heights. Scale [ca. 1:10,100,000] and [ca. 1:8,450,000].